Abnormal heavy/light chain ratio after treatment is associated with shorter survival in patients with IgA myeloma. Issue 2 (February 2017) - Suehara, Yasuhito; Takamatsu, Hiroyuki; Fukumoto, Kota; Fujisawa, Manabu; Narita, Kentaro; Usui, Yoshiaki; Takeuchi, Masami; Endean, Kelly; Matsue, Kosei
Abstract : Immunoglobulin (Ig) heavy/light chain (HLC) assays enable the separate quantification of the different light chain types of each Ig class. We retrospectively analyzed the correlation of heavy/light chain ratio (HLCR) with clinical status and its impact on outcome in 120 patients with multiple myeloma (MM). Abnormal HLCR was seen more frequently in patients with poorer myeloma response, and it appeared to be more sensitive for detecting clonality in IgA myeloma compared to IgG myeloma after treatment. Among the 85 patients who achieved ≥VGPR, the patients remained HLCR abnormal were showed significantly shorter overall survival (OS) compared to those achieving a normal HLCR (not reached vs 55.5 months, P  = 0.032). This correlation was seen in IgA myeloma patients (not reached vs 30.1 months, P  = 0.014), but not in IgG myeloma patients when patients were analyzed separately. Univariate and multivariate analysis of factors that may affect survival identified abnormal HLCR at the best response as the only independent risk factor (hazard ratio, 4.7; 95% confidence interval, 1.4 – 15.26; P  = 0.012) for shorter OS in this subset of patients. This study highlighted the HLC assay as a prognostic predictor in patients with IgA myeloma. Abstract : Immunoglobulin heavy/light chain (HLC) assay is a newer assay which can measure the different light chain types of each Ig class separately. To investigate the clinical utility of HLC assay, we measured HLC and FLC in relation to the IMWG responses in patients with IgG and IgA myeloma after treatment and evaluated its prognostic relevance.